2012
DOI: 10.3109/14764172.2012.685478
|View full text |Cite
|
Sign up to set email alerts
|

Topical 5% tranexamic acid for the treatment of melasma in Asians: A double-blind randomized controlled clinical trial

Abstract: Although lightening of pigmentation was obtained, the results were not significant between the two regimens. However, topical TA produced erythema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
57
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(74 citation statements)
references
References 17 publications
5
57
1
1
Order By: Relevance
“…8 Tranexamic acid is widely used as antifibrinolytic agent, it has recently been found to inhibit plasminogen-keratinocyte interaction which decreases tyrosinase activity leading to decrease melanin synthesis by melanocytes. 9,10 This is the first clinical study comparing single drug Tranexamic Acid in three different forms that is oral, soaks and cream in treatment of melasma. of oral tranexamic acid in treatment of melasma in Pakistani population : a pilot study conducted in 65 patients of melasma with oral tranexamic acid 250 mg twice a day for 6 months duration.…”
Section: Discussionmentioning
confidence: 99%
“…8 Tranexamic acid is widely used as antifibrinolytic agent, it has recently been found to inhibit plasminogen-keratinocyte interaction which decreases tyrosinase activity leading to decrease melanin synthesis by melanocytes. 9,10 This is the first clinical study comparing single drug Tranexamic Acid in three different forms that is oral, soaks and cream in treatment of melasma. of oral tranexamic acid in treatment of melasma in Pakistani population : a pilot study conducted in 65 patients of melasma with oral tranexamic acid 250 mg twice a day for 6 months duration.…”
Section: Discussionmentioning
confidence: 99%
“…oral, topical and localized microinjections) have shown promising results (7,(9)(10)(11), there is a lack of support for its efficacy and safety in melasma due to the absence of sufficiently powered randomized controlled trials (RCTs). Through a systematic review of the literature, we aimed to investigate the effectiveness and safety of TA, alone, or as an adjuvant, in patients with melasma.…”
mentioning
confidence: 99%
“…Four clinically heterogeneous trials were identified in the area of aesthetic surgery, involving 365 patients [39][40][41][42] but all 4 assessed the use of TXA as a lightening agent for melasma in oriental and/or Asian skin, including 2 studies investigating the use of oral TXA in conjunction with laser depigmentation. Tranexamic acid has also been reported as a constituent of tumescent solution in hair transplant surgery 43 and liposuction.…”
Section: Aestheticmentioning
confidence: 99%